Biopreservation of Fresh Strawberries by Carboxymethyl Cellulose Edible Coatings Enriched with a Bacteriocin from Bacillus methylotrophicus BM47 - Yulian Tumbarski; Radosveta Nikolova; Nadezhda Petkova; Ivan Ivanov; Anna Lante (Food Technology and Biotechnology, 2019)

(untitled)
Bacteriocins are a large group of antimicrobial compounds that are synthesized by representatives of the genus Bacillus and lactic acid bacteria. They are used extensively in the food industry as biopreservatives. Incorporated in the composition of edible coatings, bacteriocins can reduce microbial growth and decay incidence in perishable fruits, thus improving product shelf-life and commercial appearance. The present study aims to investigate the effect of edible coatings of 0.5 % carboxymethyl cellulose (CMC) enriched with a purified bacteriocin from Bacillus methylotrophicus BM47 on the shelf-life extension of fresh strawberries. During storage at 4 °C and 75 % relative humidity for 16 days, the measurements of mass loss, decay percentage, total soluble solids (TSS), titratable acidity (TA), pH, organic acids, total phenolic and anthocyanin contents and antioxidant activity were made. The results demonstrate that the application of edible coatings with 0.5 % CMC and 0.5 % CMC with bacteriocin (CMC+B) led to a significant decrease of mass loss in the treated strawberries compared to the uncoated fruit. After the 8th day of storage, significant reductions in decay percentage along with the absence of fungal growth in CMC+B-coated fruit were observed in comparison with the CMC-coated and control strawberries. During the second half of the storage period, CMC and CMC+B treatments reduced TSS amount in the coated fruit compared to the control, but did not affect the increase of TA and decrease of pH values that are normally associated with postharvest changes. The CMC and CMC+B coatings did not prevent the decrease of ascorbic acid, and total phenolic and anthocyanin contents during cold storage. The application of CMC and CMC+B coatings had a significant inhibitory effect on decreasing the antioxidant activity throughout the storage period and maintained the antioxidant levels in both treatments close to the initial value of 76.8 mmol Trolox equivalents per 100 g of fresh mass.